Equilibrium prices of the titles: Sharpe and the Securities Valuation Model (CAPM) - Gaytán Cortés, Juan (Mercados y Negocios, 2023)
The Capital Asset Pricing Model (CAPM) is a model used to calculate the profitability that an investor must demand when making an investment in a financial asset, depending on the risk he is assuming.